ANALISIS SEKTOR UNGGULAN KOTA JAMBI 2015-2024 - Ria Apriani; Rosmeli Rosmeli; Putri Intan Suri (LPPM - STIE SAKTI ALAM KERINCI, 2026)
This research aims to analyze the leading sectors and the growth dynamics of economic sectors in Jambi City during the period 2015–2024. The data used in this research are Gross Regional Domestic Product (GRDP) data of Jambi City and Jambi Province at constant prices by business field obtained from the Central Statistics Agency (BPS). The analytical methods used are Location Quotient (LQ), Dynamic Location Quotient (DLQ), Specialization Index (SI), Growth Ratio Model (GRM), and Shift Share Analysis.The results show that there are 14 basic sectors and 3 non-basic sectors based on the LQ analysis. The DLQ analysis indicates that there are 4 prospective sectors with the potential to develop in the future. The Specialization Index analysis shows that Jambi City has not specialized in a particular economic sector. Meanwhile, the results of the GRM and Shift Share analyses indicate that several sectors have relatively better growth and competitiveness than other sectors. In general, the economic structure of Jambi City is dominated by trade, transportation, services, and other urban-supporting sectors that play an important role in promoting regional economic growth. Keywords: Leading Sectors, Economic Growth.Location Quotient, Shift Share Analysis.